Design of Hardware and Software Equipment for Monitoring Selected Operating Parameters of the Irrigator - Ján Jobbágy; Oliver Bartík; Koloman Krištof; Viliam Bárek; Roderik Virágh; Vlastimil Slaný (Sensors, 2022)
The aim of this paper was to design a device for monitoring the work of irrigation technology (in our case, irrigation by sprinkler). Two devices for monitoring selected irrigation operating parameters for two hose reel irrigation machines were designed. During the monitored period of connection of the equipment to the sprinkler, 15 irrigation doses were carried out for both sprinklers. Irrigation operating characteristics working pressure, hose reel speed and selected weather conditions temperature and humidity were monitored. When evaluating the results, we proved the need to monitor the operation of the sprinkler not only by the coefficient of variation Cv, but also by introducing the coefficient of non-uniformity a. The results obtained indicate variability with respect to a particular irrigation dose and the applicable assessment method. The results were reviewed by one-way ANOVA analysis where observed coefficients and irrigation dose were considered as dependence factors. The results indicate a statistically significant impact of the applied quality coefficient of work and thus the impact of a particular device (p < 0.05, Fcrit = 2.77). When evaluating the effect of the included irrigation dose, we also showed a statistically significant effect in both facilities (p < 0.05, F = 1.92). By checking the operation of the hose reel irrigation machine, we managed to successfully apply the proposed classifications, which also perform the function of fault prediction. The proposed facilities show that proper plant operation and timely response can help create more efficient and sustainable irrigation services, not only saving water but also reducing costs for the owner.